Change of maize-soybean cropping patterns and its link with climate warming in Northeast China between 2000 and 2020 - DU Guoming, MA Mengqi, ZHANG Rui, LIU Zhengjia (Ziyuan Kexue, 2024)
[Objective] Climate warming has a significant impact on crop cultivation pattern. The purpose of this paper is to explore the relationship between climate warming and crop cultivation pattern, and to clarify the degree of contribution of different influencing factors to crop growth, so as to provide reference for regional cultivation structure adjustment and layout optimization. [Methods] Based on the 2000, 2010, and 2020 crop classification data, this study analyzed the trend of changes in maize and soybean cultivation scale and pattern under climate warming using the GIS grids and geo-information maps. The maximum entropy model was employed to reveal the main factors driving the change in the spatiotemporal crop planting patterns. [Results] (1) In terms of scale, the change in the planting area indicated an increase in maize planting area; conversely, the soybean planting area decreased. Heilongjiang Province, the largest increase in maize planting area of 69.01%, Jilin Province, the largest decrease in soybean planting area of 68.21%. (2) The transitional zone for maize and soybean cultivation in the Northeast region shifted noticeably northward between 2000 and 2020. Among them, the transition zone for maize and soybean cultivation moved northward by about 129.10 km in Songnen Plain from 2000 to 2010, and moved northward by about 283.80 km in Sanjiang Plain from 2010 to 2020. (3) The dominant bioclimatic factors influencing changes in the suitability of maize planting and the movement of planting areas in the Northeast were the average temperature of the hottest season and the average temperature of the driest season, respectively. The northern boundary of the maize and soybean planting transitional zone is mainly located within the ≥10 ℃ active cumulative temperature range of 2900-3100 ℃, and as this cumulative temperature zone continues to move northward, the planting transitional zone moves along with it. [Conclusion] The planting structure and layout of maize and soybean in Northeast China from 2000 to 2020 were significantly changed by temperature. In the future, more attention needs to be paid to the impact of climate change on crop cultivation in order to promote the sustained and healthy development of agricultural production and ensure the long-term stability of food security.